Microwave dielectric properties of (1−x)MgO–x(0.8LiF–0.2CaF2) ceramics for low-temperature Co-fired ceramics. Issue 9 (November 2015) - Wang, Xiao-Hong; Jiang, Hai; Wang, Xiao-Chuan; Li, Zhen-Lin; Lu, Wen-Zhong
Abstract: The effects of eutectic addition of 0.8LiF–0.2CaF2 on microwave dielectric properties and structure of MgO ceramics were investigated. Addition of LiF–CaF2 decreased the sintering temperature of MgO ceramics to 900 °C but did not affect the dielectric properties of the ceramics. The dielectric constant ( ε r ) and temperature coefficient of the resonant frequency ( τ f ) of MgO ceramics were not influenced by the LiF–CaF2 eutectic content within the range of 0.02–0.08. However, the quality factor ( Q×f ) was dependent on the amount of LiF–CaF2 added. Moreover, open or closed sintering condition influenced the microstructure and microwave dielectric properties of LiF–CaF2 -doped MgO ceramics. The X-ray diffraction and impedance spectroscopy analyses indicated that Li and Ca substitution for Mg and F substitution for O occurred in MgO ceramics, and a high amount of F was incorporated into the MgO lattice under closed sintering condition. Overall, 0.96MgO–0.04(0.8LiF–0.2CaF2 ) ceramics sintered at 950 °C in an open crucible exhibited excellent microwave dielectric properties of ε r =9.18, Q×f =130198 GHz and τ f =−65 ppm/°C. This study shows that eutectic addition of LiF–CaF2 effectively decreases the sintering temperature of MgO without deteriorating the ceramic performance.